2020
DOI: 10.1111/epi.16742
|View full text |Cite
|
Sign up to set email alerts
|

Increased frequency of proinflammatory CD4 T cells and pathological levels of serum neurofilament light chain in adult drug‐resistant epilepsy

Abstract: ObjectiveAdult drug‐resistant epilepsy (DRE) is associated with significant morbidity. Infiltration of immune cells is observed in DRE epileptic foci; however, the relation between DRE and the peripheral immune cell compartment remains only partially understood. We aimed to investigate differences in immune cell populations, cytokines, and neurodegenerative biomarkers in the peripheral blood of subjects with epilepsy versus healthy controls, and in DRE compared to well‐controlled epilepsy (WCE).MethodsPeripher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 49 publications
3
18
0
3
Order By: Relevance
“…Brain injury markers have attracted some interest in epilepsy. NfL levels can increase after prolonged febrile seizures in children and in older individuals with drug-resistant epilepsy [15,16]. Children with new-onset epilepsy have higher levels of S100B than controls [17].…”
Section: Introductionmentioning
confidence: 99%
“…Brain injury markers have attracted some interest in epilepsy. NfL levels can increase after prolonged febrile seizures in children and in older individuals with drug-resistant epilepsy [15,16]. Children with new-onset epilepsy have higher levels of S100B than controls [17].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Ouédraogo et al observed that compared to healthy controls, CD4 T-cell populations were more abundant in the peripheral blood of focal onset epilepsy subjects, in line with our results. 33 Author data support that epilepsy is linked to an expansion of the CD4 T cell subset, which is skewed toward a proinflammatory Th17/Th1 phenotype. Additionally, Xu et al for the first time demonstrate that proinflammatory IL-17-producing T cells gamma delta are concentrated in the epileptogenic zone, and their populations positively related to seizure severity, 34 which are corroborated by animal experiments in the brains of a mouse model of SE induced by the kainic acid displaying similar activation of adaptive and innate immune responses, in accordance with our analysis data.…”
Section: Discussionmentioning
confidence: 86%
“…While their absolute levels were similar to our study, the age-dependent slope of NFL levels was steeper in DRE than in WCE and HC. The authors linked this finding to the expanded inflammatory CD4-T cells and proinflammatory cytokine levels, which may, in the long run, drive neurodegeneration in people with DRE (14). We recently published data on the impact of acute, tonic clonic seizures (TCS) in patients with DRE on the biomarkers described here.…”
Section: Discussionmentioning
confidence: 91%
“…The authors did not find significant associations between the levels of NFL or other biomarkers and classical markers of neuroinflammations such as CSF cell count or MRI alterations (10)(11)(12)(13). Ouédrago et al (14) very recently showed elevated NFL levels in drugresistant epilepsy (DRE) when compared to well-controlled epilepsy (WCE) or healthy controls (HC). While their absolute levels were similar to our study, the age-dependent slope of NFL levels was steeper in DRE than in WCE and HC.…”
Section: Discussionmentioning
confidence: 97%